Machinability investigation of AISI 4340 steel with biodegradable oil-based MQL system. (2022) - Mawandiya, B.K.; Patel, H.V.; Makhesana, M.A.; Patel, K.M.
Abstract: The present work involves turning AISI 4340 with carbide insert under three cooing/ lubrication environments (dry condition, MQL condition, MQSL condition) to recognize the sustainable cooling or lubrication technology. Machining performance is evaluated by analyzing energy consumption, carbon emission, tool wear, and surface roughness. Two cutting speeds (100 and 140 m/min), a fixed feed rate (0.5 mm/rev), and depth of cut (0.5 mm) are used for the experiments. For MQL machining, castor oil is selected, and for MQSL, Molybdenum disulphide (MoS2 ) dispersed in sunflower oil is used as a lubricant mixture. From experimentation, the tool wear value under MQSL is the lowest compared to the other two cooling/lubrication conditions. In addition, when compared to dry conditions, the value of surface roughness for MQL is minimum, but it is found marginally higher when compared with MQSL condition. The results show that the MQSL condition is more effective than the other two conditions with enhanced machining performance.